Alternative Possibilities for Defining the Length of the Separate Left-Turn Lane at the Existing Level Intersection - Tomaž Tolazzi (Promet - Traffic&Transportation, 1970)
On the market today, there are various computer programsfor simulating traffic flows at level intersection, which are allbased on mathematics not seen by the end user. In this way theuser only supplies data without being aware of how the programworks and neither of the mathematical background. The resultsobtained are critically judged under this influence, resultingthus in subjective decisions.Therefore, the article presents simple alternative mathematicalpossibilities for the requirements and the length of aseparate left-turn lane at intersection.